Catharanthus roseus Periwinkle, Madagascar Periwinkle, Vinca: FPS112/FP112, 5/2007 - Gilman, Edward; Howe, Teresa (EDIS, 2007)
This document provides a comprehensive overview of Catharanthus roseus, commonly known as periwinkle or Madagascar periwinkle. It details the plant’s characteristics, including its height, spread, and growth habits, as well as its flowering and fruiting patterns. The document also covers the plant’s preferred growing conditions, such as soil type, light requirements, and drought tolerance. Additionally, it discusses the plant’s uses in landscaping and its potential invasive nature. The document highlights common pests and diseases that affect periwinkle and offers guidance on propagation methods. Original publication date October 1999.